Product Quality, Service Quality and Price on Buyer Satisfaction of Naavagreen Beauty Products through Sales Promotion as Intervening Variables - Erni Rusyani (Institute of Computer Science (IOCS), 2022)
Today, beauty clinics are mushrooming and popping up that offer a variety of services that suit the demands of society in the field of beauty and skin health. Navaagreen is one of the many beauty clinic businesses that aim to answer the need for beauty and skin health by utilizing raw materials derived from nature in order to achieve the company's goal of increasing client happiness and loyalty. This study is based on a survey. The participants in this research are buyers/customers who have done treatment or used products from Beauty Naavagreen clinic. The data collection technique used a questionnaire that obtained 35 respondents. In analyzing the data using (SEM-PLS) using the SMART PLS 3.0 program. The analysis carried out is by analyzing the outer model, analyzing the inner model and testing the hypothesis. The results of the study have proven that Product Quality and Service Quality have a positive effect on Sales Promotion, and Price has a positive effect on Buyer Satisfaction